Pengaruh Penambahan Jerami Dan Additive Beton Mix Terhadap Kuat Tekan Dan Lentur Beton - Finasti Finasti; Mustakim Mustakim; Andriyani Andriyani (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
The purpose of this study is to determine the properties collected from Botto Village of Sidenreng Rappang Regency in a uniform and comprehensive manner and to determine the relative strength and relative durability of concrete made using rice waste and additives using these materials. It is a complement to the practical study. The tests were carried out after 7 years of treatment, 14 days and 28 days, using 15 x 30 cm long cylindrical test tubes. It used 9 cylindrical and 2 jet models, each showing 5% and 10% difference. %. 9 cylindrical and 2 block tests were carried out for normal concrete, and 33 parameters were measured in these tests. According to the test results, the compressive strength of the concrete after 7 years with the addition of 5% grass and concrete mixture is 5.94 Mpa. and the total of 10% grass and concrete mixture is 7.83 Mpa. 14 years plus 5% grass and concrete mixture, this is 9. 06 Mpa for 10% grass and concrete mix 8.28 years plus 10.57 Mpa for 5% grass and concrete mix and 9.81 Mpa for 10% grass and concrete mix.  Key words: straw, compressive strength, concrete mix, flexural strength